TOTAL PHYSICAL RESPONSE METHOD FOR DEVELOPING PRODUCTIVE SKILLS IN PRESCHOOLERS WITHIN INCLUSIVE EDUCATION SETTINGS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This thesis examines the effectiveness of Total Physical Response (TPR) methodology in developing productive skills among preschoolers in inclusive educational environments. The research explores how TPR's kinesthetic approach supports diverse learning needs, particularly benefiting children with varying abilities, learning styles, and developmental patterns.